Penerapan Metode Pembelajaran Make A Match untuk Meningkatkan Hasil Belajar Tematik Materi Perubahan Energi Siswa Kelas III MI Islamiyah Attanwir Talun Sumberrejo - Lukman Khoirin (Attanwir : Jurnal Keislaman dan Pendidikan, 2022)
This article discusses the application of the make a match learning method to improve thematic learning outcomes of the energy change material for class III students of MI Islamiyah Attanwir Talun Sumberrejo Bojonegoro. The low learning outcomes of students in understanding the integrated thematic learning process are considered as a result that leads to the teaching process of teachers in conservative classes using the lecture method. The background of this research is the application of the make a match method to the learning of theme 6 sub-theme 2 of energy change material in class III MI Islamiyah Attanwir Talun Sumberrejo Bojonegoro. This study aims to improve student learning outcomes in the thematic learning of energy change material with the make a match learning method. Make a match is a learning method to find a partner. Each student gets a card (question or answer), then quickly find a pair that matches the card he holds. The learning atmosphere in the make a match type of cooperative learning model will be noisy, but very fun and enjoyable. Make a match learning (looking for a partner) is an active, creative, effective, and fun learning model (PAKEM), which prioritizes cooperation and speed among students to achieve learning goals. This learning model has characteristics, namely to complete the learning material, students study in groups or with other students. This study uses classroom action research (Classroom Action Research) with a research design by Kemmis and Mc Taggart which consists of two cycles, each cycle consisting of four stages, namely the planning stage, the implementation stage, the observation stage,and the reflection stage. The data collection techniques of this research are observation, test, and documentation. The subjects of this study were third grade students of MI Islamiyah Attanwir Talun Sumberrejo Bojonegoro with a total of 27 students consisting of 10 boys and 17 girls. The results of the study before using the make a match learning method on average got a percentage of 55.25%. And after using classroom action research in 2 cycles, the first cycle was 65.20% and the second cycle was 85.15%. Thus, it can be concluded that the make a match learning method can improve thematic learning outcomes of energy change material for class III students of MI Islamiyah Attanwir Talun Sumberrejo Bojonegoro.